Determinants of academic achievement among grade ten students at Menkorer secondary school, Ethiopia: the role of individual, familial and school characteristics - Demeke Wolie Ambaye (Cogent Education, 2024)
AbstractThe aim of this study was to examine the role of individual, familial and school factors in predicting students’ academic achievement. The study employed correlational design to undertake the analysis. The participants of the study were 461 grade ten students which were selected using systematic random sampling technique. Self-reported questionnaire was used to gather data. Descriptive and inferential statistics were utilized so as to analyze the data. Among the inferential statistics hierarchical multivariate regression analysis was utilized to examine the relative importance of the predictor variables on the criterion variable at each level. The finding revealed that large variance in students’ academic achievement was accounted for by individual level variables followed by familial level variables. School level variables contributed considerable variance in students’ academic achievement. In order to enhance students’ academic performance, parents and school community shall contribute their share and discharge responsibilities unconditionally.